Controlled lateral epitaxial growth in vertical β-Ga2O3 nanowires on sapphire by MOCVD. (17th May 2021) - Ma, Yongjian; Zhang, Xiaodong; Li, Junshuai; Cao, Xu; He, Tao; Zhang, Li; Tang, Wenbo; Xu, Kun; Fan, Yaming; Cai, Yong; Fu, Houqiang; Zhang, Baoshun
Abstract: Lateral epitaxial growth in vertical β -Ga2 O3 nanowires was studied on sapphire substrates via metal organic chemical vapor deposition by controlling growth temperature and O2 flow rate. The lateral epitaxial growth rate of β -Ga2 O3 rise up with increasing growth temperature and decreasing O2 flow rate, which are related to reaction kinetics and parasitic reaction, respectively. In addition, a growth model is proposed to explain the morphology of nanowires when growth condition changes. These results can provide important guidance on addressing slow coalescence rate of β -Ga2 O3 nuclear islands on heterogeneous substrates and open new doors to β -Ga2 O3 optoelectronic and electronic devices on cost-effective foreign substrates.